(3GdSHYjGJ aj ehGYX GdHQjGJs - (3eMeO Hf YHO GdQMef Hf YHO Gddg GdgeOGfj, CHh fUQs
(3ChdgG (B:s
(3bGd eMeO Hf YHO Gddg GdgeOGfi CYde Cf Ld LdGdg hJJGHYJ fYeg Rje SHY SeGhGJ hSejJg cJGH GdSHYjGJ ai ehGYX GdHQHGJ s
(3BNQgG (B:s
(3bGd jhe dGLeYI hGdLfI aCYWjJ GdLeYI hGdLfI dCeJi ced cJGH GdSHYjGJ ai ehGYX GdHQjGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(1280 (3O(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs